Efficiency of Wireless Power Transfer System with PWM Methode as Rectifier on Receiver - Zuansah Rachmat Munggaran; Mudrik Alaydrus (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
One part of the wireless power transfer system is rectifier, where the energy which received by the receiver conditioned according to the device character. While devices with direct current as a wave form of electrical energy is commonly used. Conventional rectifier was using half wave or full wave circuit where uses diode circuit, capacitor and transformer as filter. The disadvantage of the system is reactive power and harmonization. We proposed the pulse width modulation because PWM could enhanced power factor value on an AC voltage source system with 50 Hz frequency. The main focus on which this study was based was to derive efficiency values from pulse width modulation utilization in the rectification process while the frequency work at 5 MHz and highest power at 54.48 Watt, and compare this reasearch with published research for similar systems. To achieve the objectives of this study then performed design and build system, measurement and analysis of the value of system efficiency. The results of the research obtained the highest value of efficiency at 81%.